2019
DOI: 10.1210/endrev/bnz002
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Dependent Insulinotropic Polypeptide Receptor Therapies for the Treatment of Obesity, Do Agonists = Antagonists?

Abstract: Glucose-dependent insulinotropic polypeptide receptor (GIPR) is associated with obesity in human genome-wide association studies. Similarly, mouse genetic studies indicate that loss of function alleles and glucose-dependent insulinotropic polypeptide overexpression both protect from high-fat diet–induced weight gain. Together, these data provide compelling evidence to develop therapies targeting GIPR for the treatment of obesity. Further, both antagonists and agonists alone prevent weight gain, but result in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 122 publications
0
50
0
Order By: Relevance
“…Questions have been raised related to both the degree of contribution of GIPR agonism to the PD effects of dual GIP/GLP-1 RAs, and the mechanisms by which agonism of the GIPR may result in these effects. These uncertainties stem from several findings, including: 1) studies demonstrating that the impaired incretin effect in T2D is not improved by GIP infusion, even at pharmacological concentrations [10,11]; 2) the observation that in T2D, acute administration of GIP has been shown to increase secretion of the diabetogenic hormone glucagon, even during hyperglycemia [28,29]; 3) the known lipogenic effects of GIP, along with preclinical data supporting its role in promoting fat mass [30]; 4) preclinical data demonstrating weight loss in mouse and non-human primate models via GIPR antagonism [31]; 5) recent clinical data demonstrating that acute GIP infusion in patients with well-controlled T2D treated with the GLP-1 RA liraglutide resulted in an increase in plasma glucagon and glucose concentrations, and no effect on energy intake or expenditure [32]. Although these and other findings raise important questions regarding the relative contribution and the mechanism of action of GIPR agonism in a dual GIP/GLP-1 RA such as tirzepatide, there are preclinical and clinical data that support the contribution of GIPR agonism to the improvement in both glycemic and weight control [24,33].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Questions have been raised related to both the degree of contribution of GIPR agonism to the PD effects of dual GIP/GLP-1 RAs, and the mechanisms by which agonism of the GIPR may result in these effects. These uncertainties stem from several findings, including: 1) studies demonstrating that the impaired incretin effect in T2D is not improved by GIP infusion, even at pharmacological concentrations [10,11]; 2) the observation that in T2D, acute administration of GIP has been shown to increase secretion of the diabetogenic hormone glucagon, even during hyperglycemia [28,29]; 3) the known lipogenic effects of GIP, along with preclinical data supporting its role in promoting fat mass [30]; 4) preclinical data demonstrating weight loss in mouse and non-human primate models via GIPR antagonism [31]; 5) recent clinical data demonstrating that acute GIP infusion in patients with well-controlled T2D treated with the GLP-1 RA liraglutide resulted in an increase in plasma glucagon and glucose concentrations, and no effect on energy intake or expenditure [32]. Although these and other findings raise important questions regarding the relative contribution and the mechanism of action of GIPR agonism in a dual GIP/GLP-1 RA such as tirzepatide, there are preclinical and clinical data that support the contribution of GIPR agonism to the improvement in both glycemic and weight control [24,33].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The GIPR locus has been identified in genome-wide association studies to be associated with obesity and body-mass index (BMI) 6 highlighting its importance as a regulator of adiposity in humans. Alleles have been identified that both increase 7 and, more importantly, decrease BMI 8 , presenting support for potential GIPR-directed therapies as weight loss agents.…”
mentioning
confidence: 99%
“…Alleles have been identified that both increase 7 and, more importantly, decrease BMI 8 , presenting support for potential GIPR-directed therapies as weight loss agents. Furthermore, in some studies, the lower BMI alleles have been associated with either reduced expression 6 , signaling 9,10 , or incretin function 2,11,12 . In alignment with the human genetic evidence, mouse gene deletion studies of GIP, GIPR, or ablation of GIPsecreting K cells all demonstrate protection from diet-induced obesity (DIO) [13][14][15][16] .…”
mentioning
confidence: 99%
See 2 more Smart Citations